EduCity, Johor : A Promising Project with Multiple Challenges to Overcome - Wan, Chang Da, 1982-; Weerasena, Benedict (Trends in Southeast Asia ;, 2019)
EduCity, built as an integrated learning hub, is a constituent part of Malaysia's general programme to enhance its reputation as a regional centre for higher education. Located in Iskandar Malaysia, Johor, on a 305-acre catalyst development housing seven higher education institutions, EduCity aims to become a best-in-class higher education destination and at the same time provide talent to support economic activities in Iskandar Malaysia. With over 3,500 students currently enrolled, EduCity is moving towards its goal of having 16,000 students by 2025. Its proximity to Singapore and Kuala Lumpur provides it with a large population of potential students, although attracting academic staff to work there remains a challenge. Other challenges that EduCity faces revolve around the provision of facilities and support services, coordination of courses on offer, and coordination between the entity that runs the site -- EduCity Iskandar Sdn Bhd (EISB) -- and the universities.